ADMISSION TEST, AMNIOTIC FLUID INDEX, AND COLOR OF LIQUOR IN TERM PREGNANCIES IN ACTIVE LABOR AND THEIR ASSOCIATION WITH LABOR AND PERINATAL OUTCOME - DEEPA P; RAJANI P; MALAVA RANJEET (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The aim of the study was to study the admission non-stress test, amniotic fluid index, and color of liquor at term gestation in active labor in all primi gravida and multi gravida irrespective of their medical condition. Methods: An observational study was done from January 2015 to August 2016 on 200 pregnant women who were admitted for labor and delivery. A detailed examination was done and non-stress test, amniotic fluid index (AFI), and color of liquor were studied in active labor. Details of the mode of delivery and condition of the mother and the neonate were assessed at the end of each delivery. Results: The sensitivity of studying all the three parameters is 100% and specificity is 91.91%. The positive predictive value is 85.33%, negative predictive value is 100%, and accuracy is 94.58% with significant p value of <0.001. Conclusion: From this study, we can conclude that studying all the three parameters, that is, admission test, AFI, and color of liquor in term pregnancies is a reliable method to assess perinatal outcome.